Perlindungan Hukum terhadap Penumpang Meninggal Dunia di Angkutan Udara - Noor Eva Rahma; Nadhilah Alifia Maharani (CV Rewang Rencang, 2023)
Air Transportation is obliged to provide safety guarantees for its passengers. The airline as the carrier is required by law to be responsible for the loss suffered by the passenger for the loss suffered due to the operation of air transportation. Until now, there are still many incidents of air transport accidents that cause death and injuries to passengers. According to data from the Aviation Safety Network, until now in Indonesia alone, there have been 104 aircraft accidents with more than 1300 fatalities. This is the basis for the importance of further reviewing the legal protection for passengers who die in air transportation.